2010
DOI: 10.1136/ip.2010.028522
|View full text |Cite
|
Sign up to set email alerts
|

Disability, environmental factors and non-fatal injury

Abstract: Injury prevention efforts need to focus on reducing disability-related injuries and reducing environmental barriers for all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…5,7,11,12,14,17,23,30 In a study using NHIS data, Brophy et al 12 reported injury odds ratios of 1.68 and 2.98 for moderate and severe disability, respectively, which is comparable to our study's adjusted odds ratio of 2.35 for workers with disabilities for nonoccupational injuries. Furthermore, our data show a higher rate of occupational injuries among workers with disabilities than workers without disabilities.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…5,7,11,12,14,17,23,30 In a study using NHIS data, Brophy et al 12 reported injury odds ratios of 1.68 and 2.98 for moderate and severe disability, respectively, which is comparable to our study's adjusted odds ratio of 2.35 for workers with disabilities for nonoccupational injuries. Furthermore, our data show a higher rate of occupational injuries among workers with disabilities than workers without disabilities.…”
Section: Discussionsupporting
confidence: 78%
“…22 Recent work by Leff et al explored the role of environmental factors (e.g., societal attitudes, the natural environment, and policies) in the functioning and societal participation of people with disabilities. 14 Environmental factors were found to be independently associated with injury regardless of disability status; however, disability status remained a risk factor for injury, although environmental factors attenuated the association. One current conceptualization of disability, the World Health Organization's International Classification of Functioning, Disability and Health (ICF), emphasizes environmental factors and has been used in recent studies to evaluate injury risks of persons with disabilities.…”
mentioning
confidence: 99%
“…policies‚ physical/structural‚ attitude/support and services/assistance. These findings are in line with the results of previous studies (Dijkers et al, 2002;Han et al, 2005;Leff et al, 2010). Dijkers et al (2002) demonstrated that there were significant relationships between ADL and perceived environmental barriers.…”
Section: Variablessupporting
confidence: 83%
“…The results of some previous studies were in accord with these results (Dijkers et al, 2002 (Turkish participants); Ephraim et al, 2006;Leff et al, 2010;Keysor et al, 2010;Whiteneck et al, 2004). This was anticipated, because in recent years enough consideration has not been given to the transportation system, especially, providing appropriately accommodated vehicles needed by persons with disabilities and older individuals in Iran.…”
Section: Variablessupporting
confidence: 81%
See 1 more Smart Citation